The Use of Virtue and Character in Applied Ethics - Donahue, James (Horizons, 1990)
This article explores the criticism made against "virtue ethics" that it is insufficiently normative and thus is unable to assist decision makers in making practical moral choices. By assessing the claims, strengths, and weaknesses of contemporary proposals for "character ethics," the article contends that a virtue approach to ethics does yield some central moral norms. An ethical perspective that combines these norms with the insights offered by the idea of virtue itself provides a compelling framework for moral choice. A case study illustrates the claims.